2021
DOI: 10.1177/0020764021994145
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic events, post-traumatic stress disorders, and gender among Yazidi population after ISIS invasion: A post conflict study in Kurdistan – Iraq

Abstract: Background: Traumatic experiences can lead to a range of mental health problems such as depression, anxiety and post-traumatic stress disorder. The prevalence of post-traumatic stress disorder depends on the cumulative exposure to traumatic stress. The Yazidis (Êzidî) are a Kurdish religious minority living in the north of Iraq, western Iran, eastern Turkey, and northern Syria. Islamic State of Iraq and Syria (ISIS) had sought to destroy the Yazidis population through killings; sexual slavery, enslavement, tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Females who reached adolescence were often separated from males, after which they were used as slaves serving the ISIS commanders and were sexually abused repeatedly [ 25 ]. As a result, Iraqi IDP women and young girls present with high levels of PTSD [ 26 ]. A study of Yazidi women and children, 16% of whom had survived enslavement, found that over 80% met clinical criteria for a DSM-5 PTSD diagnosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Females who reached adolescence were often separated from males, after which they were used as slaves serving the ISIS commanders and were sexually abused repeatedly [ 25 ]. As a result, Iraqi IDP women and young girls present with high levels of PTSD [ 26 ]. A study of Yazidi women and children, 16% of whom had survived enslavement, found that over 80% met clinical criteria for a DSM-5 PTSD diagnosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, limited attention has been given to post‐conflict effects. In the extant literature, psychological diagnoses (primarily post‐traumatic stress disorder; e.g., Al Shawi & Hassen, 2022) and the experiences of children and refugees (e.g., Newnham et al., 2018; Quosh et al., 2013) are often explored. More limited attention has been paid to factors that may increase the resilience of adults who live in a culture whose recent history is characterised by a climate of conflict (for exceptions, see, e.g., Alfadhli & Drury, 2016; Cowden et al., 2023; Cummings et al., 2012; Dushimirimana et al., 2014; Zraly & Kagoyire, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extreme brutality, the continuous danger and the long-term displacement of large groups of the population within the country, psychological problems and mental illness are particularly common here. Approximately 79% of Yazidi internally displaced persons (IDPs) in a refugee camp in the KRI reported PTSD symptoms ( 21 ). Among Syrian refugees in northern Iraq, a prevalence of 35–38% for PTSD related to trauma and torture was found by Ibrahim and Hassan ( 7 ).…”
Section: Introductionmentioning
confidence: 99%